Demographic factors and open defecation practices: A cross-sectional study in Gunungtua Jae Village, Padang Lawas Utara - Lubis, Rini Khofifah; Wisudawan B, Owildan; Ahmad, Haslinah (Jurnal Prima Medika Sains, 2024)
Open defecation (OD) remains a significant public health concern, particularly in rural areas of developing countries. This study aimed to investigate the association between demographic factors and OD practices in Gunungtua Jae Village, Padang Lawas Utara, Indonesia. A cross-sectional study was conducted involving 82 households. Data were collected using structured questionnaires and analyzed using Chi-square test and logistic regression. The findings revealed a significant association between several demographic factors and OD practices. These factors included household head knowledge (p = 0.000), occupation (p = 0.002), attitude (p = 0.000), education level (p = 0.000), and income level (p = 0.000). The study highlights the importance of considering demographic factors when addressing OD practices in public health interventions. Comprehensive efforts are needed to enhance community knowledge, particularly among household heads, regarding the significance of adequate sanitation and the detrimental impacts of OD practices. Collaboration between community health centers (puskesmas) and various stakeholders is essential for the sustainable implementation of the Total Sanitation Based on Community Approach (STBM) program. This program can effectively raise awareness and promote positive behavioral changes towards environmental hygiene and personal health, with a primary focus on encouraging proper sanitation practices and preventing environmental pollution.